Dismantling Multicomponent Behavioral Treatment for Insomnia in Older Adults: A Randomized Controlled Trial - Epstein, Dana R. (Associated Professional Sleep Societies, LLC, 2012)
STUDY OBJECTIVE: Recently, the use of multicomponent insomnia treatment has increased. This study compares the effect of single component and multicomponent behavioral treatments for insomnia in older adults after intervention and at 3 months and 1 yr posttreatment. DESIGN: A randomized, controlled study. SETTING: Veterans Affairs medical center. PARTICIPANTS: 179 older adults (mean age, 68.9 yr ± 8.0; 115 women [64.2%]) with chronic primary insomnia. INTERVENTIONS: Participants were randomly assigned to 6 wk of stimulus control therapy (SCT), sleep restriction therapy (SRT), the 2 therapies combined into a multicomponent intervention (MCI), or a wait-list control group. MEASUREMENTS AND RESULTS: Primary outcomes were subjective (daily sleep diary) and objective (actigraphy) measures of sleep-onset latency (SOL), wake after sleep onset (WASO), total sleep time (TST), time in bed (TIB), and sleep efficiency (SE). Secondary outcomes were clinical measures including response and remission rates. There were no differences between the single and multicomponent interventions on primary sleep outcomes measured by diary and actigraphy. All treatments produced significant improvement in diary-reported sleep in comparison with the control group. Effect sizes for sleep diary outcomes were medium to large. Treatment gains were maintained at follow-up for diary and actigraph measured SOL, WASO, and SE. The MCI group had the largest proportion of treatment remitters. CONCLUSIONS: For older adults with chronic primary insomnia, the findings provide initial evidence that SCT, SRT, and MCI are equally efficacious and produce sustainable treatment gains on diary, actigraphy, and clinical outcomes. From a clinical perspective, MCI may be a preferred treatment due to its higher remission rate. CLINICAL TRIAL INFORMATION: Behavioral Intervention for Insomnia in Older Adults. NCT01154023. URL: http://clinicaltrials.gov/ct2/show/NCT01154023?term=Behavioral+Intervention+for+Insomnia+in+Older+Adults&rank=1. CITATION: Epstein DR; Sidani S; Bootzin RR; Belyea MJ. Dismantling multicomponent behavioral treatment for insomnia in older adults: a randomized controlled trial. SLEEP 2012;35(6):797-805.